Modification of industrial BOF slag: Formation of MgFe 2 O 4 and recycling of iron - Xue, Peng; He, Dongfeng; Xu, Anjun; Gu, Zongxi; Yang, Qixing; Engström, Fredrik; Björkman, Bo (Journal of alloys and compounds, 2017)
Efficient recycling of iron oxide from industrial BOF (basic oxygen furnace) slags has always been an issue in metallurgy. In this study, a new method was developed for the efficient recycling of iron oxide: It was transformed into magnesioferrite spinel (MgFe 2 O 4 ) by mixing the industrial BOF slag with 6.00% SiO 2 first, and then the modified slag got cooled down from 1400 °C to 1270 °C at a rate of 1 °C/min. Finally, the Fe resources were recycled by magnetic separation. Various experiments and analyses such as XRD, SEM–EDS analyses, Factsage thermodynamic simulation, magnetization characterization, dry magnetic separation, and chemical analysis were carried out. The results show that the obtained MgFe 2 O 4 has a high melting point (1716.76 °C in theory) and ferromagnetism (specific magnetic susceptibility of (8.03–206.84) × 10 −5  m 3 /kg). Therefore, it could be separated from the weakly magnetic industrial BOF slag (specific magnetic susceptibility of (0.024–0.136) × 10 −5  m 3 /kg). Furthermore, this new method could be applied to different BOF slags. The yield of MgFe 2 O 4 increased to above 80% when the content of Fe 2 O 3 was in the range 25.81–46.90%. After the modification and magnetic separation, the total Fe content increased by 15.80%, from 21.20% in the industrial BOF slag to 37.00% in the magnetic slag. This is better than the direct magnetic separation of iron oxide without any treatment. The magnetic slag could be reused as either a sintering or slag splashing material. The nonmagnetic slag can be used to produce high value-added building materials. Hence, this new method can be used to recycle the iron oxide from industrial BOF slags, achieving the sustainable development of the iron and steel industry.